Genetic incorporation of unnatural amino acids for the synthesis of proteins with defined modifications - Bi, Xiaobao (2015)
Residue-specific incorporation and site-specific incorporation methods are widely used to incorporate an increasing number of novel unnatural amino acids (UAAs) into proteins with great potential to facilitate their structure-function studies. This dissertation presents my work on the genetic incorporation of several UAAs by using these two methods into proteins and their applications in the synthesis of proteins with defined modifications, which are important for understanding their role in cellular events. These two methods together with other protein synthesis and modification techniques are introduced in Chapter 1 of this thesis. In chapter 2, a residue-specific incorporation method was used to incorporate azidonorleucine (ANL) and azidonorvaline (ANV) into proteins via methionine auxotrophic strain. The genetically incorporated ANL served as the orthogonal lysine precursor in the protein, onto which one ligatable auxiliary group was installed for native chemical ubiquitination. The semisynthesis of diubiquitin and its characterization was demonstrated. To further expand the utility of our method, ubiquitylated H2A was also synthesized efficiently in a similar way, which was used to study the behavior of several deubiquitinases towards it and the crosstalk between H2A ubiquitination and H3K36 methylation. In this chapter, we also attempted to develop one new method to prepare arginine methylated protein using genetically incorporated ANV. One mutant MetRS that can efficiently activate ANV was found. Several guanidinylating reagents were synthesized and tested for the site-specific guanidinylate ion at the protein level. The pyrrolysyl-tRNA synthetase (PylRS)/PylT pair has been wildly used to incorporate site-specifically UAAs into proteins in E. coli. In chapter 3, several pyrrolysine analogs were shown to be incorporated into proteins via orthogonal PylRS/PylT pair. One genetically incorporated α-hydroxyl amino acid was used to synthesize protein α-thioester by utilization of cysteinyl prolyl ester (CPE) auto-activating motif on protein. The proposed formation of diketopiperazine thioester via an intramolecular N–S acyl shift reaction was not successful possibly due to the steric hindrance of the α-hydroxyl amino acid located in our CPE motif. One genetically incorporated Cbz-protected homocysteine was used to synthesize histones with two different modifications by orthogonal cysteine-based chemistry. One model H3 protein was shown to be installed efficiently with a dimethylated lysine mimic at K27. The attempt to install the second modification into H3 failed due to the poor efficiency of the deprotection of Cbz-protected homocysteine using silver acetate or iodine in the acetic acid buffer. In the last part of this chapter, to incorporate more new UAAs into protein using PylRS/tRNA pair, the two plasmids based selection system was established in our lab. The construction and functional test of two plasmids used in the positive and negative selections were presented. Two libraries of mutant PylRS was constructed and successfully used to screen the mutant that can recognize the pyrrolysine analogs.